A DELAY-DEPENDENT STABILITY CRITERION FOR LINEAR NEUTRAL SYSTEMS WITH TIME-VARYING DELAY. (2012) - RATCHAKIT, G.; SANGKAPATE, P.; PATTRARATIP, T.; SEEDARAT, P.; SATSANIT, W.; RATCHAKIT, M.
No abstract available